PEMASARAN KOPI SECARA DIGITAL DAN STRATEGI BISNIS DALAM PANDEMI COVID-19 - William Dhamawan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Indonesia is located in a geographical area, therefore many areas are used as coffee plantation land. Coffee in Indonesia has a rapid economic impact, it is proven that the number of coffee shop businesses in the city of Bandung is likely to expand. This study was conducted to find out coffee marketing strategies in the midst of the Covid-19 pandemic. The object of this research is a coffee shop that is developing and hit by the pandemic. The business that is focused on this research is Old Ben's Garage and Coffee a business that has a digital markerting model by utilizing social media, and as well as utilizing instant courier delivery. Old Ben's Garage and Coffee also has a website to provide information to consumers. This research uses a qualitative approach with an interpretive paradigm aimed at determining the right marketing strategy. By implementing a 7P marketing mix strategy as well as SWOT (Product, Price, Place, Promotion, people, Physical Evidence, Process). This research shows that Old Ben's Garage and Coffee can survive by optimizing digital marketing strategies during the Pandemic.